2017
DOI: 10.1021/acs.chemrestox.7b00171
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and Mitochondrial DNA Methylation Patterns Induced by Valproic Acid in Human Hepatocytes

Abstract: Valproic acid (VPA) is one of the most widely prescribed antiepileptic drugs in the world. Despite its pharmacological importance, it may cause liver toxicity and steatosis through mitochondrial dysfunction. The aim of this study is to further investigate VPA-induced mechanisms of steatosis by analyzing changes in patterns of methylation in nuclear DNA (nDNA) and mitochondrial DNA (mtDNA). Therefore, primary human hepatocytes (PHHs) were exposed to an incubation concentration of VPA that was shown to cause ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 60 publications
(115 reference statements)
2
18
0
Order By: Relevance
“…In a separate study using primary human hepatocytes, hypomethylation of seven mitochondrial genes was observed upon VPA treatment and within the same study, two nuclear genes crucial for DNA methylation, DNMT and MAT (methionine adenosyltransferase), were found to be hypermethylated, resulting in reduced levels of the DNMT enzymes and SAM. This may impact mtDNA methylation downstream, which is suggestive of crosstalk between the nucleus and mitochondria after VPA exposure (Wolters et al, 2017). The downstream molecular events after VPA exposure were also explored in human hepatocytes, where upregulation of DNMT caused transient hypermethylation in mtDNA and downregulation of mitochondrial proteins resulting in impaired mitochondrial function.…”
Section: Impact Of Xenobiotics On Mtdna Methylationmentioning
confidence: 99%
“…In a separate study using primary human hepatocytes, hypomethylation of seven mitochondrial genes was observed upon VPA treatment and within the same study, two nuclear genes crucial for DNA methylation, DNMT and MAT (methionine adenosyltransferase), were found to be hypermethylated, resulting in reduced levels of the DNMT enzymes and SAM. This may impact mtDNA methylation downstream, which is suggestive of crosstalk between the nucleus and mitochondria after VPA exposure (Wolters et al, 2017). The downstream molecular events after VPA exposure were also explored in human hepatocytes, where upregulation of DNMT caused transient hypermethylation in mtDNA and downregulation of mitochondrial proteins resulting in impaired mitochondrial function.…”
Section: Impact Of Xenobiotics On Mtdna Methylationmentioning
confidence: 99%
“…The data presented in this DIB demonstrate induced steatosis pathways by all DMRs during VPA-treatment, covering interesting drug-induced steatosis genes (persistent DMRs upon terminating VPA treatment and the EP300 network). This was illustrated in our associated article (Wolters et al, 2017) [1] . MeDIP-seq raw data are available on ArrayExpress (accession number: E-MTAB-4437).…”
mentioning
confidence: 71%
“…1 B-C) and the gene names, gene symbols, and fold changes (FCs) of those neighbors were shown in Table 3 . A more detailed description of those findings can be found in Wolters et al [1] .
Fig.
…”
Section: Datamentioning
confidence: 97%
“…Facilitated by transcriptomic and epigenomic approaches, this in vitro culture system revealed interactions between alterations in DNA methylation and mRNA expression changes during the development of AFB1-induced hepatocellular carcinoma (Rieswijk et al 2016) and revealed the persistent changes in gene expression and microRNA expression in response to CsA-associated cholestasis (Wolters et al 2016). Wolters et al (2017Wolters et al ( , 2018 and Van Breda (van Breda et al 2018) also used the sandwich-cultured PHH and multiple omics approaches (transcriptomics, epigenomic and proteomics) to examine the roles of epigenetic factors in liver steatosis development induced by repeated exposures (3-5 days) to valproic acid (VPA), a drug to treat epilepsy and bipolar disorders. Through the integrative cross-omics analyses, they discovered several treatment-initiated reactions (e.g.…”
Section: Primary Human Hepatocytes (Phh)mentioning
confidence: 99%
“…Through the integrative cross-omics analyses, they discovered several treatment-initiated reactions (e.g. the cross-talk between nuclear DNA and mitochondrial DNA hypermethylation (Wolters et al 2017), the persistent epigenetic and transcriptomic alterations in the mitochondrial genome coupled with the measurable mitochondrial dysfunction (Wolters et al 2018) and the inhibition of nuclear receptors at DNA methylation and mRNA levels (van Breda et al 2018), deepening the understanding of the VPA-induced hepatosteatosis.…”
Section: Primary Human Hepatocytes (Phh)mentioning
confidence: 99%